English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
0

-3X+(-5X)-9=
-3(-5)+[-5X-5]-9
-15+-25
=-40--9
=-39

2006-10-06 10:51:42 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

What exactly do you need help with?

To correct your mistakes:

-3(-5)+[-5(-5)]-9=15+25-9=31.

2006-10-06 11:01:14 · answer #1 · answered by James L 5 · 0 1

sorry
this does not make sense

this does:
-3X+(-5X)-9=-8x-9
if x = -5, then
-8(-5)-9
=40-9=31

2006-10-06 18:52:18 · answer #2 · answered by locuaz 7 · 0 0

-3x+(-5x)-9
-8x-9

if x = -5
-8(-5)-9
40-9
31

2006-10-06 18:01:54 · answer #3 · answered by danjlil_43515 4 · 0 0

fedest.com, questions and answers